Analisis Penerapan Kurikulum Merdeka Belajar dalam Pembelajaran Pendidikan Jasmani pada Siswa SMK Texar Karawang - Sukma Annisa Pratiwi; Rina Marlina; Febi Kurniawan (Peneliti.net, 2023)
This study aims to determine the application of the Merdeka Belajar Curriculum to the learning of Sports and Health Physical Education for students of SMK Texar Klari Karawang. The factor of curriculum renewal needs to be considered so that student learning can improve from any aspect. It is felt that it is necessary to analyze the application of the Merdeka Belajar Curriculum, so that teachers can find out the level of application of the Merdeka Belajar Curriculum to students. This research uses a descriptive qualitative approach with survey research methods. The population used by all students of SMK Texar Klari with research samples of students who were willing to fill out the questionnaire. Research instrument for the Questionnaire on the Application of the Independent Learning Curriculum. Data analysis using validity tests and descriptive statistics. Based on the results of the study, it is known that the student questionnaire is declared reliable. Statistics show that overall it is said to be high with a percentage of 75%. Likewise in the aspects of skills, knowledge, utilization, movement development and aspects of the Pancasila Profile.